COMPARATIVE GEOCHEMISTRIES OF PDII AND PTII: - FORMATION OF MIXED HYDROXYCHLORO AND CHLOROCARBONATO-COMPLEXES IN SEAWATER - Cosden J.M.; Byrne R.H. (My University, 2003)
Comparative observations of PdII and PtII hydrolysis in chloride solutions indicate that [PdCl3OH2-]/[PdCl42-] and [PtCl3OH2-]/[PtCl42-] concentration ratios in salinity 35 seawater (S = 35) are smaller than one at a typical surface ocean pH (~8.2), and are larger than one at pH = 8.2 when S < 10. The hydrolysis behaviors of PdCl42- and PtCl42- are very similar. In 0.5 M NaCl at 25°C the hydrolysis constant for both elements, written in the form β1 = [MCl3OH2-][Cl-][H+][MCl42-]-1, is logβ1*=-8.97. Between ionic strengths 0.3 M and 1.0 M for PdII and between 0.1 M and 1.0 M for PtII, log β1 is within approximately 0.1 units of the value appropriate to 0.5 M NaCl. This small dependence of PdCl42- and PtCl42- hydrolysis constants on ionic strength is consistent with predictions based on expected activity coefficient behavior.Carbonate is observed to complex PdCl42- significantly, but to a smaller extent than OH- under conditions appropriate to seawater. Complexation of PtCl42- by CO32- was observed in this work but the rate of complexation was too slow to allow equilibrium observations. The principal dissimilarity between the chemistries of PdII and PtII in our investigation was the sharp contrast in observed PdII and PtII reaction rates. Differences in reaction kinetics may cause fractionation of PdII and PtII in the environment. The speciation of PtII, unlike PdII, is likely to be based on chemical environments experienced by PtII over a period of days, and perhaps weeks.